2003
DOI: 10.1037/0090-5550.48.2.109
|View full text |Cite
|
Sign up to set email alerts
|

Psychological distress in workers with traumatic upper or lower limb amputations following industrial injuries.

Abstract: Workers' Compensation Board of British ColumbiaObjective: To determine whether individuals with traumatic upper limb amputations would report more symptoms of posttraumatic stress disorder (PTSD) and depression than individuals with traumatic lower limb amputations. Study Design: Retrospective file review. Setting: CARF-accredited outpatient rehabilitation center. Participants: Thirty workers with unilateral upper limb amputations and 25 workers with unilateral lower limb amputations. Main Outcome Measures: Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 11 publications
0
18
1
Order By: Relevance
“…Levels of anxiety and depression may be elevated in the acute period (28-51%) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). It has been suggested that there is a dramatic reduction in psychological symptoms (anxiety and depression) 2 months after discharge from the rehabilitation ward.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Levels of anxiety and depression may be elevated in the acute period (28-51%) (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). It has been suggested that there is a dramatic reduction in psychological symptoms (anxiety and depression) 2 months after discharge from the rehabilitation ward.…”
Section: Discussionmentioning
confidence: 97%
“…Prosthesis use has been shown to be correlated with increased quality of life (5,37). High anxiety and depression levels have been determined in the acute period in amputees (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In addition to studies suggesting that longterm depression and anxiety decrease in patients undergoing rehabilitation (25)(26)(27)(28)(29), others have proposed that these remain elevated even after many years (30)(31)(32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%
“…As such, they can potentially address both functional [3] and cosmetic [4] user needs and have positive psychosocial implications [5][6][7][8][9]. However, the actual impact of these technologies on patients' lives has been documented in only two case reports [10][11].…”
Section: Introductionmentioning
confidence: 99%
“…First, the cause of the health condition may be a traumatic event. Examples of this may include burns (DiFede and Barocas, 1999;DuHamel, Difede, Foley, & Greenleaf, 2002;Van Loey, Maas, Faber, & Taal, 2003;Stoddard et al, 2006), spinal cord injuries (see Chapter 10), or traumatic amputations (Cheung, Alvaro, & Colotla, 2003;Cavanagh, Shin, Karamouz, & Rauch, 2006). In these examples, the event causing the injury may induce posttraumatic stress symptoms, even if the person had not sustained the injury.…”
Section: Disease Onsetmentioning
confidence: 99%